Embedding social development in the Ateneo De Naga University's development communication program - Bana, Ma. Filipinas H. (The Philippine Journal of Development Communication, 2017)
This paper presents and describes the development communication program of the Ateneo de Naga University as a promising component of a university's social service function. The study focused on the social service aspect of the program by looking into the specific ways by which it fulfills the university's social service role through its three-fold function of instruction, research, and social extension. It also evaluated the present status of the program vis-a-vis the ideals of social development. The research participants included faculty members who served as key informants and select groups of students from the 2nd, 3rd, and 4th year levels. Case study, key informant interviews, and focus group discussion were the main strategies used in this research. Data were sourced from both primary data (transcribed interview protocols) and secondary data (documents), which were then analyzed using case study, secondary data analysis, and content analysis.